Pembangunan instrumen penilaian akhlak pelajar di institusi pengajian tinggi awam - Abdul Latif, Adibah (2013)
This study is designed to develop Students’ Akhlak Evaluation Instrument (IMPAK) in higher education institutions. The instrument is focused on three constructs which are behaviour, oral communication and personality. The instrument items were developed from two main references that are al-Qur’an and Intipati Ihya’ Ulumuddin by Imam al-Ghazali. The constructs and their definitions were obtained from structured interviews of five lecturers who specialize in akhlak field. The instrument was pilot tested on 60 students from one local university to find the validity and reliability of the instrument. Based on the results of the pilot test, the rating scale was changed from 5 to 4 subscales and 12 items were omitted. The reliability test used test retest technique. The first test was administered at the start of the semester and the second test was administered three months later. The survey research was conducted on 400 students from four public universities. The data was analyzed using Rasch Measurement analysis. The findings showed that IMPAK has good construct validity. Item and individual reliability was very high and the rating scale was understood by the students. The constructs were unidimensional and 64 items remain fit with the model. The IMPAK was free from gender bias. Generally, the level of students’ akhlak was at good logit achievement. There is no significant difference in akhlak level across races and educational stream. It is recommended that relevant entities such as students, parents, higher education and MOHE establish a mechanism for developing well-rounded students especially in affective domain.